1968
DOI: 10.1007/bf02530964
|View full text |Cite
|
Sign up to set email alerts
|

Positional distribution of fatty acids in depot triglycerides of aquatic animals

Abstract: Stereospecific triglyceride analyses were performed on fats of the following animals: five aquatic invertebrates, five freshwater fish, six marine fish, three marine birds, two amphibia, two seals, a whale, and a marine turtle. The distribution of faty acids was asymmetrical in most cases. A formula is presented which describes the general tendencies of fatty acid distribution in many animal fats, and some special rules which modify this formula are stated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
3
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(75 citation statements)
references
References 10 publications
5
65
3
2
Order By: Relevance
“…6 Litchfield reported that the positional distribution of 22:6n-3 and 22:5n-3 in fish TAG can be predicted by the following proportionality equations: 7 y 1 = 0.28x, y 2 = 2.06x, and y 3 = 0.66x, where x shows the mole% of 22:6n-3 or 22:5n-3 in the total TAG (0 < 5 x < 30); and y 1, y 2, and y 3 show the mole% of these fatty acids in the sn-1, sn-2, and sn-3 positions, respectively. These relationships indicate that about 10, 70, and 20% of 22:6n-3 and 22:5n-3 were esterified in the sn-1, sn-2, and sn-3 positions, respectively.…”
Section: Investigations 25mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Litchfield reported that the positional distribution of 22:6n-3 and 22:5n-3 in fish TAG can be predicted by the following proportionality equations: 7 y 1 = 0.28x, y 2 = 2.06x, and y 3 = 0.66x, where x shows the mole% of 22:6n-3 or 22:5n-3 in the total TAG (0 < 5 x < 30); and y 1, y 2, and y 3 show the mole% of these fatty acids in the sn-1, sn-2, and sn-3 positions, respectively. These relationships indicate that about 10, 70, and 20% of 22:6n-3 and 22:5n-3 were esterified in the sn-1, sn-2, and sn-3 positions, respectively.…”
Section: Investigations 25mentioning
confidence: 99%
“…5 The distributions of long-chain polyunsaturated fatty acids such as 22:6n-3, 22:5n-3, and eicosapentaenoic acid (20:5n-3; EPA) in fish TAG were detailed in many reports. [6][7][8] Previously the authors analyzed 15 flesh and liver TAG of flathead flounder, and reported that 24:6n-3 was located almost evenly among the three positions. 4 However, the analytical procedure was later revealed to be unsuitable for the analysis of fish TAG.…”
mentioning
confidence: 99%
“…In humans, the coefficient of digestibility of the most common vegetable oils in 97-98%. Only hydrogenated oils, comprising high amounts of saturated and isomeric fatty acids, have lower coefficients (Deuel, 1955 (Deuel, 1955 (Brockerhoff et al, 1968 (Chen et al, 1985;Carlier et al, 1991) (Kinsella, 1991). Secondly, the L-FABP (liver-fatty acid binding protein) present in enterocytes, contrary to the I-FABP (intestinal-FABP), might exhibit higher affinity for PUFA than for others (Lowe et al, 1987) (Sprecher, 1981).…”
Section: Dietary Sources Of Essential Fatty Acidsmentioning
confidence: 99%
“…This technique was used to successfully reveal the distribution of fatty acids at each sn position in plant oil, animal fat, milk fat, fish oil, and hen egg. For example, uneven distributions of highly unsaturated fatty acids HUFAs at the sn-2 position of TAG in fish oil and at the sn-1 and 3 positions in seal oil were reported 6 . However, intact molecular species of TAG positional isomers and enantiomers were not separated in this work.…”
Section: Introductionmentioning
confidence: 99%